Proceedings of the 36th Annual ACM/IEEE Design Automation Conference 1999
DOI: 10.1145/309847.310050
|View full text |Cite
|
Sign up to set email alerts
|

Improving the test quality for scan-based BIST using a general test application scheme

Abstract: In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 7 publications
(3 reference statements)
1
23
0
Order By: Relevance
“…It has been shown that applying different numbers (k) of capture cycles after each scan sequence (k captures per scan) can produce patterns with different signal probability profiles at the scan flip-flops [19]. Patterns which matches a specific signal probability profile can improve the detection for some stuck-at faults but deteriorate the detection for others comparing to the pseudo random patterns.…”
Section: A Path Delay Faults Testing For Scan-based Bistmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that applying different numbers (k) of capture cycles after each scan sequence (k captures per scan) can produce patterns with different signal probability profiles at the scan flip-flops [19]. Patterns which matches a specific signal probability profile can improve the detection for some stuck-at faults but deteriorate the detection for others comparing to the pseudo random patterns.…”
Section: A Path Delay Faults Testing For Scan-based Bistmentioning
confidence: 99%
“…Patterns which matches a specific signal probability profile can improve the detection for some stuck-at faults but deteriorate the detection for others comparing to the pseudo random patterns. In order to increase the overall circuit random testability, in [19] the entire test process is divided into multiple test sessions. In each test session, patterns with a specific signal probability profile are generated by applying a unique number of capture cycles after each scan sequence.…”
Section: A Path Delay Faults Testing For Scan-based Bistmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier works on built-in test generation for scan circuits using tests of the form (SI i ,T i ) were based on random patterns [9]- [11]. The methods of [9] and [10] do not achieve complete fault coverage, and all three methods do not guarantee that complete fault coverage would be achieved.…”
Section: Introductionmentioning
confidence: 99%